2013
DOI: 10.1590/s0104-11692013000300019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quality of life among persons with lung cancer, before and after the chemotherapy treatment

Abstract: although the patients have an improvement of their QLRH and symptoms related to the lung cancer after the chemotherapy treatment, there was a worsening of the symptoms which resulted from the toxicity of the chemotherapy medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
2
7
0
2
Order By: Relevance
“…This result is consistent with the literature (de Oliveira et al, 2013;Helsing et al, 1998) and may be because of the positive and negative effects of chemotherapy canceling out each other. The physical symptoms and psychological problems of the participants in this study both showed some improvements and some worsening.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the literature (de Oliveira et al, 2013;Helsing et al, 1998) and may be because of the positive and negative effects of chemotherapy canceling out each other. The physical symptoms and psychological problems of the participants in this study both showed some improvements and some worsening.…”
Section: Discussionsupporting
confidence: 93%
“…In this research, the relationship between health and quality of life became evident when the participants referred to the pain in the final stage of the disease, confirming the close analogy of the construct with the perception of physical well-being -data confirmed by recent studies on patients with advanced cancer who had the quality of life affected by the severity of the disease and the diversity of symptoms (14)(15) .…”
Section: Discussionsupporting
confidence: 83%
“… 6 A lower level of quality of life in lung cancer patients is often associated with severe symptoms of lung cancer such as fatigue, dyspnea, and poor physical functioning (PF). 5 8 …”
Section: Introductionmentioning
confidence: 99%